Addendum zu Lindan (γ‐1, 2, 3, 4, 5, 6‐Hexachlorcyclohexan) [BAT value documentation in German language, 2019]. Issue 4 (13th November 2019) - Brinkmann, B.; Drexler, H.; Hartwig, A.
Abstract: In 2018, the German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated lindane. The critical toxic effects of lindane are immunotoxic and immunomodulating effects. After inhalation exposure a NOAEC of 0.6 mg/m 3 (rat) and 1 mg/m 3 (mouse) for histological changes of the spleen, thymus and bone marrow and a NOAEL of 0.45 mg/kg body weight for rats and 2 mg/kg body weight for mice for immunological effects can be derived. Exposure to the MAK value of 0.1 mg/m 3 results in a daily intake of 0.014 mg/kg body weight (100% inhalation absorption, 70 kg body weight and 10 m 3 respiratory volume) for humans excluding skin contact. In this low concentration range, an inhibition of immunological responses is not likely. So the MAK value of 0.1 mg/m 3 was confirmed. No data are available to correlate the concentration of lindane in the air with its concentration in serum. There are no indications that immunotoxic effects occur at a serum concentration of 25 µg lindane/l, therefore, the BAT value of 25 µg lindane/l is confirmed. The NOAEL for developmental toxicity after oral application is 10 mg/kg body weight and day corresponds to 900 µg/L serum concentration. The distance of the NOAEL for developmental toxicity relating to serum concentration in rats is 40‐fold of the BAT‐value. Therefore, lindane is assigned to Pregnancy Risk Group C.